¿Con o sin ancestros? Vigencia de lo ancestral en la Amazonía peruana - Mouriès, Thomas (Pontificia Universidad Católica del Perú. Fondo Editorial, 2014)
The existence —or not— of the concept of ancestors in the indigenous Amazon has been the subject of much debate. However, regional leaders do not hesitate to call upon ‘ancestral’ knowledge, customs, or territories in the sense that, from an academic point of view, could appear enigmatic. «Ancestral, but… with or without ancestors?» is the question a confused anthropologist might ask. In this article, I propose to offer elements of a response to this question,based on a case study in Peru. First I analyze how Amazonian indigenous leaders, following international law, have adopted the legal notion of ‘ancestral possession’ of their territory to adapt it to the political sphere. This approach accounts for the recent generalization and uniformization of the term ‘ancestral’, but poses the problem of how it articulates with the indigenous cosmologies that it supposes to reflect. For this reason, I explore in the second section the pertinence of the category of ‘ancestor’ in the indigenous Amazon, briefly drawing upon the academic debate in order to define inwhat way this category takes on meaning. Based on testimony from an experienced Awajún leader, we thus return in the third section more explicitly to the different meanings and planes of reference that unfold when one uses the term ‘ancestral’, showing how Amazonian indigenous people not only adopt external conceptual elements and arguments, but also transform them based on their own cosmological singularities and political perspectives.

La existencia o no de ancestros en la Amazonía indígena ha sidoobjeto de importantes debates. Sin embargo, los líderes de la región no dudan en llamar ‘ancestrales’ sus saberes, normas o territorios,en un sentido que, desde un punto de vista académico, puede parecer enigmático. «Ancestrales, pero… ¿con o sin ancestros?», preguntaría entonces, confuso, el antropólogo. En este artículo propongo aportar elementos de respuesta a estapregunta a través del caso peruano. Primero analizo cómo los líderes indígenas amazónicos, conectándose al circuito del derecho internacional, adoptan la noción jurídica de ‘posesión ancestral’ del territorio para adaptarla al ámbito político. Este planteamiento rinde cuenta de la generalización y uniformización reciente del vocablo ‘ancestral’ pero deja pendiente el problema de su eventual articulación con las cosmologías indígenas que pretende reflejar. Por eso, en la segunda parte, intento sondear sobre la pertinenciade la categoría de ‘ancestro’ en la Amazonía indígena, recordando brevemente el debate académico para ir definiendo en qué medida esta categoría puede cobrar sentido. A partir del testimonio de un experimentado líder awajún, la tercera parte permite, entonces, volver más explícitos los diferentes sentidos y planos referenciales que despliega la referencia a lo ancestral, mostrando cómo los indígenas amazónicos no solo adoptan elementos conceptuales y discursivos externos, sino que al mismo tiempo los transforman a partir de sus propias singularidades cosmológicas y perspectivas políticas.
With or without ancestors? Validity of the ancestral in the Peruvian Amazon
Keywords: Amazonía; Ancestralidad; Awajún; Ayahuasca; Convenio 169; Corte Interamericana de Derechos Humanos; Cosmologías indígenas; Derechos de los pueblos indígenas; Discurso político; Estado; Jurisprudencia; Liderazgo; Ontología política; Perú; Política indígena; Territorialidad indígena; https://purl.org/pe-repo/ocde/ford#5.04.03